Assessment of Treatment Response of Iraqi Patients with Membranoproliferative Glomerulonephritis with Emphasis on Renal Function and Proteinuria Regression - Faiz Rashid Abayechi (Diyala Journal of Medicine, 2019)
Background: Membranoproliferative glomerulonephritis (MPGN) is a pattern of glomerular injury with characteristic light microscopic changes. It can be primary idiopathic renal disease or secondary to chronic infections, autoimmune diseases and complements dysregulation.